CAMPUR KODE DALAM TULISAN TEKS DESKRIPSI PADA SISWA KELAS VIIE SMPN 2 SUNGAI RAYA - Hilda, Desvina; Heryana, Nanang; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the use of one language into another language or the so-called mixed code. The study was conducted in SMP Negeri 2 Sungai Raya in class VII E amounted to 34 students. This study is devoted to mixed code, mixed code type, and the cause of code interference. The method of research is descriptive method with qualitative form. Research data in the form of mixed codes of form, type, and factors causing the interference code. The source of research data is the student's writing in the form of description text. Technique of collecting research data using test technique. The data collection tool uses a test sheet. Data analysis technique using qualitative descriptive technique. The results found 52 mixed code. Described by code mixed form consisting of 34 tangible words, 9 tangible phrases, 6 tangible baster, 1 tangible word, and 2 tangible idioms. Then, a mixed code type consisting of 34 types of mixed code into and 18 mixed code out. And the code-causing factor caused by the speaker consists of 49 mixed codes due to the prestige motive and 3 mixed codes due to the urgent need and mixed code due to the language of 16 mixed codes in the use of more popular terms, 34 mixed codes in the variety and level of speech, and 3 mix code in the limitations of code usage. Keywords: Code-Mixing, Student’s Writing, Descriptive Text.